Expression Profile of Circular RNAs in Oral Squamous Cell Carcinoma - Shao, Yanxiong; Song, Yuhan; Xu, Siming; Li, Siyi; Zhou, Haiwen (Frontiers in Oncology, 2020)
Background: Circular RNAs (circRNAs) are involved in the pathogenesis of many diseases. Among oral maxillofacial cancers, oral squamous cell carcinoma (OSCC) has the highest incident. However, the role of circRNAs in OSCC is still not clear. We aim to evaluate the circRNA expression profile in OSCC and further explore the potential role of circRNAs in the pathogenesis of OSCC. Methods: The circRNAs microarray analysis was performed in 6 pairs of samples of OSCC and normal oral mucosa tissues. Expression of selected circRNAs was validated by qRT-PCR. GO and KEGG analysis were performed and correlations between circRNAs and miRNAs were predicted. Results: The results showed that there were 122 differentially expressed circRNAs. 8 out of 10 selected circRNAs were validated by qRT-PCR. GO and KEGG analysis indicated identified DE circRNAs might be involved in the progression of OSCC. Among these, hsa_circSENP2, which has been validated by qRT-PCR, is a novel circRNA. Conclusions: In conclusion, our study revealed the possible role of circRNAs in the pathogenesis of OSCC, and pointed out the direction for further finding out new biomarkers of OSCC.